PENGARUH FREKUENSI PEMBERIAN AIR DAN DOSIS PUPUK KOTORAN AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KAILAN (Brassica oleraceae var. Alboglabra) - Sri Ritawati; Imas Rohmawati; Ai Nispatullaila (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2014)
This research was aimed to know the response of frequency of plant watering and a dose of chicken manure fertilizer on kailan crops. This research was conducted at trial garden Singamerta Ciruas BPTP Banten from June to August 2014. This study used a Randomized Completely Block Design with two factors. The first factor was the frequency of the plant watering with four levels: F1= frequency of plant watering once a day, F2 =frequency of plant watering 2 days, F3 = frequency of plant watering 3 days, F4 = frequency of plant watering 4 days. The second factor was dose of chicken manure fertilizer with four level: P0 = without chicken manurefertilizer (control), P1 = 10 tonnes ha-1 (23.66 g per polybag), P2: 20 tonnes ha-1 (47.33 g per polybag), P3 = 30 tonnes ha-1 (71.00 g per polybag). Eachtreatment was repeated three times, so retrieved 48 the experimental units. The parameters observed were plant height, number of leaves, plant fresh weight, root fresh weight, root dry weight, and plant dry weight. The resultsshowed that frequency of water one day once tend to provide real influence on the parameters of the age of 35 DAP plant height (30.13 cm), number ofleaf age 35 DAP (11.67 strands), plant fresh weight (93.78 g), weight wet roots (9.19 g), root dry weight (2.87 g), and plant dry weight (12.40g). Provision of chicken manure fertilizer with a dose of 47.33 g (20 tonnes ha-1) significant effect on the parameters of the plant fresh weight (96.84 g).